Short-term Outcome of Plasma Adsorption Therapy in Amyotrophic Lateral Sclerosis: Plasma Adsorption Therapy in Amyotrophic Lateral Sclerosis - Li, Bin; Zhang, Wei; Zhong, Shaoxin; Pan, Jianyi; Wang, Xiaohong; Zou, Hequn; Dou, Xianrui (Journal of Medical Biochemistry, 2022)
Background: To observe the short-term outcome of plasma adsorption（PA）therapy in amyotrophic lateral sclerosis (ALS).  Methods: 28 cases of ALS patients were recruited in this study, of which 20 were male and 8 were female with a mean age of 53.21 ±9.07 years and the average course of 33±23.35 months. The clinical manifestations were limb weakness (N=27), muscular atrophy (N=27), muscular tremor (N=5), dysphagia (N=12) and dysarthria (N=12). The clinical data of the patients recruited were graded by Amyotrophic Lateral Sclerosis Functional Rating Scale Revised (ALSFRSR) : 40 (N=5). All patients received PA therapy once a week for three successive times after examining the conditions of blood coagulation and virus infection. PA therapy was supplemented with neurotrophic therapy meanwhile. All patients' clinical manifestations and scores of ALSFRSR before treatment and one week after treatment were evaluated and compared. The levels of serum superoxide dismutase (SOD), interleukin-10 (IL-10), serum creatine kinase (CK) and lactate dehydrogenase (LDH) before and after treatment were compared. Results: After PA therapy, 14 patients have improved obviously in muscle strength, 4 patients in hypermyotonia partially, 3 patients in muscular tremor, 5 patients in dysarthria, 3 patients in salivation to some extent and 2 patients in swallowing function. The score of ALSFRSR after PA treatment (31.89±10.36) was remarkably higher than that before PA treatment (30.68±10.52) (P
Keywords: Amyotrophic lateral sclerosis; Plasma adsorption; Therapeutic effect